Literature Study: Relationship Between the Availability of Health Human Resources (HR) and the Implementation of Service Programs at Health Centers - Dewi Agustina; Nadilla Fitri Yanni; Rizkya Salsabila Simanjuntak; Ummu Mawaddah Ikrimah Damanik; Putri Sima; Maulidya Hanafiah; Jihan Khalifi; Nadia Maimunah Tarihoran; Mei Linda; Fahmi Idris Siregar; Mawadah Karunia; Audya Putri Az-Zahra; Rahma Fadhila; Defani Zasqiyah Putri; Nabila Zahrah; Nur Indah Hasibuan; Mahmudin Hasibuan (Universitas Muhammadiyah Palu, 2026)
The availability of health human resources (HR) is an important factor in determining the success of the implementation of service programs at health centers. This study aims to analyze the relationship between the availability of health human resources and the implementation of service programs in health centers through a literature study approach. The method used is literature review by reviewing various relevant national and international scientific articles. Data collection was carried out through searching databases such as Google Scholar, PubMed, and ScienceDirect using keywords related to health human resources and health center services. The selected articles were then analyzed in a qualitative descriptive manner. The results of the study show that the availability of health human resources, both in terms of quantity, distribution, quality, and management, has a significant relationship with the implementation of service programs at health centers. Limited number of health workers, uneven distribution, and high workload are the main obstacles in service optimization. In addition, the competence of health workers and facility support also affect the effectiveness of service programs which include promotive, preventive, and curative. In conclusion, the availability of adequate and evenly distributed health human resources is very necessary to improve the quality of services at health centers. Therefore, better planning and management of human resources is needed to support the improvement of public health status.